Proceedings of the 9th International Conference on Predictive Models in Software Engineering 2013
DOI: 10.1145/2499393.2499395
|View full text |Cite
|
Sign up to set email alerts
|

Training data selection for cross-project defect prediction

Abstract: Software defect prediction has been a popular research topic in recent years and is considered as a means for the optimization of quality assurance activities. Defect prediction can be done in a withinproject or a cross-project scenario. The within-project scenario produces results with a very high quality, but requires historic data of the project, which is often not available. For the cross-project prediction, the data availability is not an issue as data from other projects is readily available, e.g., in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(103 citation statements)
references
References 24 publications
1
101
0
1
Order By: Relevance
“…(1) Source selection algorithm for software project defect prediction Prediction of cross project software defects, between source and target attribute measure distribution project project there is a certain correlation [5] , so the maximum minimum value, and the mean and standard deviation of 4 data distribution data to define the feature vector of the C project. To help achieve the feature similarity sort source and target selection of software project project the distribution of software module is a module attribute, expressed as C = {c max , c min , c mean , c std }, the distribution characteristics of each project data attribute values can be used in c(F m (S))to represent the feature vector of the S project, which can be defined as follows:…”
Section: Software Defect Prediction Modelling For Network Cloud Develmentioning
confidence: 99%
“…(1) Source selection algorithm for software project defect prediction Prediction of cross project software defects, between source and target attribute measure distribution project project there is a certain correlation [5] , so the maximum minimum value, and the mean and standard deviation of 4 data distribution data to define the feature vector of the C project. To help achieve the feature similarity sort source and target selection of software project project the distribution of software module is a module attribute, expressed as C = {c max , c min , c mean , c std }, the distribution characteristics of each project data attribute values can be used in c(F m (S))to represent the feature vector of the S project, which can be defined as follows:…”
Section: Software Defect Prediction Modelling For Network Cloud Develmentioning
confidence: 99%
“…The first one is to apply the data filtering method to find the best suitable training data (e.g., [8,9,12,14]). For example, Turhan et al [8] proposed a nearest neighbor (NN) filter to select cross-company data.…”
Section: A Defect Predictionmentioning
confidence: 99%
“…After Briand et al made an early attempt to validate the applicability of CPDP [14], many researchers in this field have tried to improve the performance of CPDP models using different techniques such as data mining and machine learning. Fortunately, recent studies have shown that it is indeed a feasible method for defect prediction in software projects with different sizes [13,[15][16][17][18][19][20]. Due to space limitations of this paper, for more details about CPDP approaches, please refer to the latest surveys [6,7].…”
Section: Related Workmentioning
confidence: 99%